2006
DOI: 10.1111/j.1439-0434.2006.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of A New Almond Witches’ Broom Phytoplasma in Iran

Abstract: Almond witchesÕ broom (AlmWB) is a destructive disease in several provinces in Iran. Association of phytoplasma with the disease has been established previously. In the present work two phytoplasmas from Khafr (KAlmWB) and Neyriz (NAlmWB) in the Fars Province were compared by biological and molecular analysis. Both infected bitter almond, wild almond, peach and nectarine but not apple and pear, by grafting. In bitter almond the symptoms induced by KAlmWB consisted of severe proliferation, internode shortening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 14 publications
(17 reference statements)
2
45
0
1
Order By: Relevance
“…Phytoplasma phoenicium" [15,16]. In this study, we showed that a phytoplasma is associated with peach yellows symptoms in Kurdistan province of Iran that showed 98% sequence homology with almond witches' broom phytoplasma, "Ca.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Phytoplasma phoenicium" [15,16]. In this study, we showed that a phytoplasma is associated with peach yellows symptoms in Kurdistan province of Iran that showed 98% sequence homology with almond witches' broom phytoplasma, "Ca.…”
Section: Discussionmentioning
confidence: 87%
“…Almond witches' broom has been reported as a widespread and devastating disease in Iran and Lebanon [16,17]. It can spread rapidly and kill trees at any age within 2 -3 years [17] and transmitted by dodder to peach and nectarine trees in greenhouse condition [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only two other phytoplasma in this sub group viz. phytoplasma associated with K. arvensis phyllody in Italy [18] and almond witches'-broom in Iran [21]. The 23S rRNA gene has not been sequenced completely for most of the phytoplasmas [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…Em plantas lenhosas, como é o caso da primavera, é comum a ocorrência de infecção com baixo título de fitoplasma, como já registrado para outras espécies como Rubus fruticosus , olmo (Ulmus spp) , macieira (KARTTE; SEEMUELLER, 1991), e videira (CREDI, 1994 Uma vez que os fitoplasmas não são cultiváveis em meio de cultura, a cuscuta tem se mostrado útil nos trabalhos envolvendo este tipo de patógeno. A transmissão destes agentes de plantas doentes para plantas sadias é um das formas de se demonstrar a sua patogenicidade e confirmar diagnoses feitas com base na sintomatologia, como tem sido relatado em diversos trabalhos (COUSIN et al, 1986;CARRARO et al, 1988;CARRARO et al, 1991;CREDI;SANTUCCI, 1992;LOI et al, 1995;SEEMULLER, 1997;SALEHI;IZADPANCH;HEYDARNEJAD, 2006). A transmissão de fitoplasmas a partir de seu hospedeiro original para plantas de vinca através da cuscuta também tem sido utilizada quando estes fitoplasmas ocorrem em baixas concentrações, pois a sua passagem para vinca pode facilitar sua detecção, bem como servir para a manutenção de coleções de fitoplasmas para uso futuro (MARCONE et al, 1999).…”
Section: Sequenciamento Do 16s Rdna Do Fitoplasmaunclassified